2018
DOI: 10.15252/msb.20177823
|View full text |Cite
|
Sign up to set email alerts
|

Genomics of cellular proliferation in periodic environmental fluctuations

Abstract: Living systems control cell growth dynamically by processing information from their environment. Although responses to a single environmental change have been intensively studied, little is known about how cells react to fluctuating conditions. Here, we address this question at the genomic scale by measuring the relative proliferation rate (fitness) of 3,568 yeast gene deletion mutants in out‐of‐equilibrium conditions: periodic oscillations between two environmental conditions. In periodic salt stress, fitness… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
15
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(15 citation statements)
references
References 69 publications
0
15
0
Order By: Relevance
“…To test the generality of our observations we analyzed the dataset of Salingon et al (Salignon et al 2018) who studied the single-gene deletion library in two types of fluctuating environments using serial batch cultures and bottlenecking. In one of the fluctuating conditions (temporal variation in methionine concentration) we observed the same trend as our study.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…To test the generality of our observations we analyzed the dataset of Salingon et al (Salignon et al 2018) who studied the single-gene deletion library in two types of fluctuating environments using serial batch cultures and bottlenecking. In one of the fluctuating conditions (temporal variation in methionine concentration) we observed the same trend as our study.…”
Section: Resultsmentioning
confidence: 99%
“…In general, experimental microbial evolution studies have focused on genetically homogeneous populations and the effect of de novo mutation. However, a small number of studies have made use of genetically heterogeneous populations to address effects of environmental fluctuations (Salignon et al 2018). To the best of our knowledge, all studies of microbial evolution reported to date have used batch culture, which requires serial passaging and population bottlenecking, adding additional variables to the study design.…”
Section: Introductionmentioning
confidence: 99%
“…The limited understanding of microbial response to fluctuating environments comes mainly from single-species studies. The selection for mutations in fluctuating environments has been extensively studied in theory [21][22][23][24][25], showing that complex interactions between the dynamics of the environment and the dynamics of adaptation can affect selection. In addition, experimental studies have shown that fluctuating environments have a profound effect on selection for antibiotic resistance [26][27][28], suggesting that rapid fluctuations could avoid the evolution of resistance.…”
Section: Introductionmentioning
confidence: 99%
“…Environments can, of course, vary slowly and recent experiments have shown the impact of rate of change in the environment on the population fitness (Salignon et al, 2018;Boyer and Sherlock, 2019). The fixation probability, fixation time and adaptation rate in changing environments have also been studied in a number of theoretical work (Takahata et al, 1975;Gillespie, 1993;Mustonen and Lässig, 2008;Assaf et al, 2008;Uecker and Hermisson, 2011;Waxman, 2011;Peischl and Kirkpartick, 2012;Cvijović et al, 2015;Dean et al, 2017), and it has been found that when the environment changes at a finite rate, the population dynamics are strongly determined by the environment in which the mutant arose.…”
Section: Introductionmentioning
confidence: 99%